A Social Science Program in General Education. - Eddy, G. Norman (Harvard Educational Review)
Boston University can be justly proud of its College of General Education established in 1946. General Education as conceived by Boston University is concerned not only with the common educational needs of all students and their development as intelligent, human beings but also with breaking down some of the artificial and arbitrary boundaries to learning. The college attempts to achieve this goal by giving the student a cultural frame of reference and then practical experience in evaluating social problems, thus enabling him to apply a broader perspective to the solution of contemporary social issues. In this article, Dr. Eddy, who is Chairman of the Department of Human Relations at the College of General Education, shows how integration is achieved in the social science program and how this course may be adapted to the needs of general education.